RNA-Seq Comprehensive Analysis Reveals the Long Noncoding RNA Expression Profile and Coexpressed mRNA in Adult Degenerative Scoliosis - Shi, Xin; Li, Panpan; Wu, Xiang; Wang, Zhihua; Zhao, Gang; Shu, Jun (Frontiers in Genetics, 2022)
Objective: Owing to the intensification of the aging process worldwide, the prevalence of adult degenerative scoliosis (ADS) is increasing at an alarming rate. However, genomic research related to the etiology of ADS is rarely reported worldwide. Since long noncoding RNAs (lncRNAs) play a pivotal role in the progression of human diseases, this study aimed to investigate ADS-associated messenger RNAs (mRNAs) and lncRNAs by RNA sequencing (RNA-seq), as well as performed comprehensive bioinformatics analysis based on the lncRNA–mRNA coexpression network and protein–protein interaction (PPI) network. Methods: Initially, six whole blood (WB) samples were obtained from three ADS and three nondegenerative lumbar trauma patients who underwent surgical operation for RNA-seq exploration to construct differential mRNA and lncRNA expression profiles. Subsequently, quantitative RT-PCR (qRT-PCR) was performed to validate three randomly selected differentially expressed mRNAs and lncRNAs derived from the nucleus pulposus (NP) tissue of 14 other subjects (seven ADS patients and seven nondegenerative lumbar trauma patients), respectively. Results: A total of 1,651 upregulated and 1,524 downregulated mRNAs and 147 upregulated and 83 downregulated lncRNAs were screened out from the RNA-Seq data, which constructed coexpression networks to investigate their regulatory interactions further. GO gene function prediction revealed that lncRNA-targeted genes might play a vital role in ADS via participation in multiple biological processes such as the AMPK signaling pathway, lysosomes, and ubiquitin-mediated proteolysis, as well as cellular metabolic processes. Moreover, the expression levels of three selected lncRNAs and mRNAs were validated by qRT-PCR, respectively, demonstrating that the relative expression levels were consistent with the RNA-seq data. Notably, the dysregulated RNAs, AKT1, UBA52, PTPN12, and CLEC16A, were significantly differentially expressed in ADS WB samples and might serve as potentially regulated genes for research in the future. Conclusions: This study provides the first insight into the altered transcriptome profile of long-stranded noncoding RNAs associated with ADS, which paves the way for further exploration of the clinical biomarkers and molecular regulatory mechanisms for this poorly understood degenerative disease. However, the detailed biological mechanisms underlying these candidate lncRNAs in ADS necessitate further elucidation in future studies.